Design and implementation of a GSM-integrated fire awareness system using MQ-2 and Arduino - Mat Yunus, Nor Asiah; Che Hassan, Che Zaidi; Abdul Rashid, Razali (Jurnal Penyelidikan Sains Sosial, 2025)
This paper discusses the design and development of trapped awareness that is based on ‘Global System for Mobile communications (GSM)’ signal from the phone message. The microcontroller that connects with smoke detector are placed in device and respond when a trapped awareness perceives smoke. The trapped awareness is a device which senses the smoke and if smoke is detected it beep loudly. When smoke signal gets detected from microcontroller it sends signal through ‘Tx Rx transmitter’ to GSM signal receiver. The microcontroller connect with the smoke detector, GSM system and alarm system. The device achieved this by being able to receive signals from outside the building thus indicating what necessary action to be taken place in the area where the device is installed as a fire hazard indicator. The trapped awareness which detect the smoke, usually used as appliances at buildings. The experimental setup finally proves that the device is functioning well.